Global tycoon - Ang, Yew Jun (2016)
The goal of every business is to hit the global market. Most of them start small and eventually grow, with some businesses progressing at a much slower pace in an ethical eco-friendly way, while some others grow rapidly at the expense of the environment. The latter contribute vast amounts of carbon emission and harmful gases (Goldenberg, 2013), causing climate change. In addition, failure to dispose their waste products in appropriate and adequate ways may contribute to water pollution (Renter, 2014). The question, despite knowing the harmful consequences their unethical business operations may cause to our natural environment, why do they remain so persistent in their ways? Are they perhaps too eager to profit from the demands of the rear-end consumers? Because they carry the mentality that solo efforts will not be of much impact? Or perhaps they are simply not educated in the fields of global warming. Bearing these questions in mind, my project revolves around the idea of raising awareness towards the various environmental problems and their causes, while educating the public on global warming issues.